Effect of warm compresses combined with lavender aromatherapy on body temperature among children with febrile seizures - Erwina Dwi Kristanti; Edy Soesanto; Heny Siswanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Febrile seizures are among the most common neurological emergencies in children and are closely associated with a rapid increase in body temperature. Prompt fever management is essential to reduce the risk of recurrent seizures and other complications. In addition to pharmacological treatment, complementary non-pharmacological interventions such as warm compresses and lavender aromatherapy have been suggested to enhance fever management. However, evidence regarding the combined effectiveness of these interventions remains limited. Purpose: To determine the effect of warm compresses combined with lavender aromatherapy on body temperature among children with febrile seizures treated in the emergency department. Methods: This study employed a quasi-experimental pretest–posttest control group design. A total of 32 children with febrile seizures were recruited using purposive sampling and allocated into an intervention group (n=16) and a control group (n=16). The intervention group received warm compresses combined with lavender aromatherapy, while the control group received routine care. Body temperature was measured before and after the intervention using a digital thermometer. Data were analyzed using paired t-tests to evaluate within-group differences and independent t-tests to compare outcomes between groups, with a significance level of p<0.05. Results: The mean body temperature in the intervention group decreased significantly from 39.1 ± 0.62°C before the intervention to 37.1 ± 0.62°C after the intervention (p<0.001), representing a mean reduction of 2.0°C. In contrast, the control group showed a non-significant decrease from 38.8 ± 0.45°C to 38.6 ± 0.45°C (p=0.051). Comparison between groups demonstrated a statistically significant difference in body temperature reduction (p<0.001). Conclusion: Warm compresses combined with lavender aromatherapy were effective in reducing body temperature among children with febrile seizures. This intervention may be considered a complementary nursing strategy for fever management in pediatric emergency settings to support conventional treatment.